PERAN DAN FUNGSI LEMBAGA PENYULUHAN PERTANIAN (PERKEBUNAN) TERHADAP PEBANGUNAN PERTANIAN DI KABUPATEN BULUKUMBA PROVINSI SULAWESI SELATAN - Hamadal, Rusdi; Adil, Muh. (COMPETITIVENESS, 2019)
This research aims to find out the role and function of extension institutions on agricultural development (plantations) in Bulukumba Regency, South Sulawesi Province and what obstacles in the extension and contribution of extension workers to agricultural development. This research was carried out in Bulukumba Regency using qualitative methods with data collection techniques through observation and interviews with farmers, agricultural extension workers and counseling in the Department of Food Crops, Horticulture and Plantation in Bulukumba Regency.The results of the study showed the role and fugsi of plantation agricultural counseling institutions towards agricultural development which includes as a service, central communication, central institutional development and central development of partnerships and functions of counseling institutions as planning and depreciation of programs, provision and dissemination of information, human resources development, administrative arrangement and evaluation functions have not been maximal. The lack of quantity and quality of agricultural extension workers (plantations), the lack of trainings attended by plantation extension workers, the policy of transitioning from extension workers to extension workers of food crops. Agricultural development (plantation) is also seen from economic growth, community welfare, and increasing plantation production. The decline in production in several commodities, namely cloves, rubber, cocoa and coffee based on data from the central statistics agency from bulukumba district year 2014 to 2017.    Keywords: Role and Function of Counseling Institutions, on Agricultural Development.